2013
DOI: 10.1177/1049732313488837
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Etiology of Prescription Opioid Abuse

Abstract: Although studies on the initiation of substance abuse abound, the body of literature on prescription opioid abuse (POA) etiology is small. Little is known about why and how the onset of POA occurs, especially among high-risk populations. In this study we aimed to fill this important knowledge gap by exploring the POA initiation experiences of 90 prescription opioid abusers currently in treatment and their narrative accounts of the circumstances surrounding their POA onset. This research was conducted within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 40 publications
(49 reference statements)
6
38
0
1
Order By: Relevance
“…These findings are similar to the larger body of research documenting how often women initiate drugs within social or romantic contexts [7,20,33].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are similar to the larger body of research documenting how often women initiate drugs within social or romantic contexts [7,20,33].…”
Section: Discussionsupporting
confidence: 82%
“…Similar to other findings of those trying prescription medications for the first time, some of our participants reported misusing their own legitimate prescriptions [5,8,16,20]. Among our sample, young men with sport injuries tended to initiate via oral routes and in isolation; it is likely that peers norms associated with use learned within a social context seem to create a situation by which alternate routes are taught by others.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Legitimate prescriptions leading to addiction and then use of illicit drug sources is a pathway that may be more prevalent amongst those experiencing chronic pain (Rigg and Murphy, 2013). …”
Section: Literature Reviewmentioning
confidence: 99%
“…After cannabis, youth consistently identify POs as the most commonly misused drug (Johnston, O’Malley, Bachman, & Schulenberg, 2012) and the 2013 US Centre for Disease Control national survey of American high schools found that over 20% of grade 12 students have misused prescription drugs (Kann et al, 2014). In addition to concerns regarding increased risk of morbidity and mortality associated with PO use (Frank et al, 2015, Hall et al, 2008, Office of the National Drug Control Strategy, 2011, Okie, 2010, USCDCP, 2011, USCDCP, 2012, Roy et al, 2004, Silva et al, 2013, Warner et al, 2011 and Zosel et al, 2013), there are also signals from qualitative, retrospective and cross-sectional studies that PO use may facilitate transitions to injection drug use; however, the impact of PO misuse on the incidence of initiation into injecting has not been characterized (Lankenau et al, 2012, Mars et al, 2014, Peavy et al, 2012, Rigg and Murphy, 2013, Young et al, 2012 and Young and Havens, 2012). The objective of this longitudinal study was to examine the relationship between PO misuse and time to injection initiation within an open prospective cohort of street-involved youth in Vancouver, Canada.…”
Section: Introductionmentioning
confidence: 99%